PUASA TANGGAL SEMBILAN MUHARAM (TASU‘A) PERSPEKTIF HADIS NABI SAW. - Muhammad Irfan (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2021)
This study was conducted to determine the hadith history regarding fasting on the ninth of Muharram which includes the source of the hadith, the quality of the hadith, and the interpretation of the hadith. This type of research is literature study. The main literature is the books of standard hadith or mu'tabara>t, while the secondary data is the book of syarah hadith and literature that has a relationship with this research study. Hadith history was collected using the method of takhri>j al-hadi>sṪhe quality of the hadith is determined based on the authenticity of the hadith. The substance or understanding of the hadith is explored using a hadith approach such as asba>b al-wuru>d, linguistic studies, and so on. The results of the study concluded that the hadith about fasting on the ninth of Muharram is found in the standard hadith book or mu'tabara>t with valid or acceptable quality. The conclusion of the various interpretations of the hadith is that fasting on the ninth of Muharram is intended to differentiate between the 'a>syu>ra>' fast (ten Muharram) carried out by Muslims with other religious people who also fast on that day.